Role of lipid profile and uterine artery doppler in predicting risk of preeclampsia in early second trimester - Chopra, Sheena; Pahwa, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Preeclampsia is associated with adverse pregnancy outcome and is a major cause of the fetomaternal morbidity and mortality. This study aimed at finding the role of lipid profile and uterine artery Doppler as a reliable predictor of risk of preeclampsia in early second trimester. Methods: This study is conducted in the obstetrics and gynecology department of a tertiary care teaching hospital, Amritsar. Lipid profile and Uterine artery doppler is estimated in 100 antenatal women from 14-20 weeks of period of gestation who met the inclusion criteria and are followed up till delivery or till preeclampsia sets in. Results: Out of 100 subjects 74 remained normotensive (Group A) and 26 developed preeclampsia (Group B). The mean serum level of total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL) and very low-density lipoprotein cholesterol (VLDL) was significantly higher in Group B as compared to group A women. The Preeclamptic women showed significant fall in high density lipoprotein cholesterol (HDL) level as compared to normal pregnant women. The mean S/D ratio, PI and RI values of uterine artery Doppler were higher for group B and were statistically significant. Conclusions: The combined predictive value of lipid profile and uterine artery Doppler for estimating risk of preeclampsia was more reliable than of any of the test individually.